Ionic Transport and Thermodynamic Interaction in Precision Polymer Blend Electrolytes for Lithium Batteries. Issue 22 (17th October 2021) - Kim, Kyoungmin; Nguyen, Nam; Marxsen, Stephanie F.; Smith, Sage; Alamo, Rufina G.; Kennemur, Justin G.; Hallinan, Daniel T.
Abstract: Single‐ion conducting polymer electrolytes are of interest for use with advanced battery electrodes such as lithium metal, but achieving sufficiently high conductivity has been challenging. In this work, a model system containing charged sites that are precisely spaced along the polymer backbone is explored. Precision sulfonated poly(4‐phenylcyclopentene) lithium salt ( p 5PhS‐Li) with a high degree of sulfonation (> 90%) is synthesized and blended with poly(ethylene oxide) (PEO) to investigate the thermodynamic and transport properties. Melting point depression is measured via differential scanning calorimetry, ionic conductivity, κ, is determined using electrochemical impedance spectroscopy, and the fraction of current carried by Li + is estimated based on steady‐state current measurements. In conjunction with a density measurement, melting point depression is used to find an effective Flory–Huggins interaction parameter, χ eff = − 0.21, suggesting miscibility of the blend. κ spans a large range from 2 × 10 −11 to 2 × 10 −7 S cm −1 over the composition and temperature range investigated. The fraction of charge carried by lithium ions also spans a significant range from 0.12 in majority PEO blend to 0.98 in majority p 5PhS‐Li blend. This study addresses several limitations of sulfonated polystyrene and opens up the possibility of precisely controlling the spacing of other anion types. Abstract : Polymer blends comprising varying amounts of precision polymer electrolyte and lithium‐solvating polymer are investigated for miscibility in addition to Li‐ion transference and conductivity. Insight on the mechanism of ion transport as a function of blend composition is discussed.